POTENSI PEMANGSAAN PREDATOR REDUVIIDAE (Rhinocoris fuscipes F.) TERHADAP Helicovepa spp - Sanjaya, Yayan (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2005)
In agriculture environment needed a support the crop to increase product and environment support to improvement of a product which done holisticly. The pesticide Application minimize still has a priority, replace with insect entomofagus, mikroorganisme entomopatogen and parasitoid for environment stabiliy. Natural Enemy population including predator have the very specific and unique ability for the interaction of with the prey, population of host and it can as regulator. The methode used by survey to farm area in Semudang and rear it at lab and also observe the yhe prey behaviour. The result show that the predator (Rhinocoris fuscipes F.) is needed H. armigera as. a prey abouat 5 or more for each day. The Rhinocoris fuscipes F. Rhinocoris fuscipes F. has an active behaviour to prey H. armigera.